2010
DOI: 10.1007/s11064-010-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

R-Deprenyl: Pharmacological Spectrum of its Activity

Abstract: Deprenyl has been discovered by Knoll and co-workers. The R-enantiomer of deprenyl (selegiline) is a selective and irreversible inhibitor of the B-isoform of monoamine oxidase (MAO-B) enzyme. Due to its dopamine potentiating and possible neuroprotective properties it has an established role in the treatment of parkinsonian patients. By inhibiting MAO-B enzyme, R-deprenyl decreases the formation of hydrogen peroxide, alleviating the oxidative stress also reduced by increased expression of antioxidant enzymes (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 95 publications
1
8
0
Order By: Relevance
“…Deprenyl-induced enhancement of hypothalamic dopaminergic activity with subsequent secretory suppression of the tumor growth-promoting pituitary hormone PRL may be responsible for our findings, similar to its actions in other mammary tumor models [1,3,19,20]. Inhibition of dopamine uptake into the neuron and increase in the firing-rate of dopaminergic neurons may also be contributory to the enhancing effects of deprenyl on hypothalamic dopaminergic activity similar to its effects in the striatum [12,13]. …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Deprenyl-induced enhancement of hypothalamic dopaminergic activity with subsequent secretory suppression of the tumor growth-promoting pituitary hormone PRL may be responsible for our findings, similar to its actions in other mammary tumor models [1,3,19,20]. Inhibition of dopamine uptake into the neuron and increase in the firing-rate of dopaminergic neurons may also be contributory to the enhancing effects of deprenyl on hypothalamic dopaminergic activity similar to its effects in the striatum [12,13]. …”
Section: Discussionsupporting
confidence: 63%
“…L -Deprenyl, a monoamine oxidase inhibitor, has been used as a therapeutic agent in Parkinson's and Alzhei-mer's disease because of its ability to increase the availability of catecholamines, augment the activities of antioxidant enzymes (superoxide dismutase, catalase and glutathione peroxidase) and growth-factor biosynthesis, and improve neuronal survivability [11,12,13,14]. Previously, we demonstrated that the administration of deprenyl or its metabolite, desmethyldeprenyl, to old male rats reversed the age-related decline in splenic NA innervation and enhanced splenic concanavalin A (Con A)-induced interleukin (IL)-2 production and NK cell activity [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…* p < 0.05 compared to control, # p < 0.05 compared to the LDD group. neurotropic, and immunostimulatory properties (Magyar et al 2010). It is known that deprenyl can upregulate activities of anti-oxidant enzymes such as SOD and CAT in brain dopaminergic regions (Kitani et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The monoamine oxidase inhibitors (MAO-Is) are used clinically as PD therapeutic agents (85). By inhibition of dopamine metabolism, MAO-Is decrease the formation of H 2 O 2 (41,114). Furthermore, MAO-Is also protect against asynuclein toxicity (26).…”
Section: Potential Therapeutic Approachesmentioning
confidence: 99%